An efficient self-healing key distribution scheme - Tian, Biming; Han, Song; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Self-healing key distribution schemes enable a group user to recover session keys from two broadcast messages he received before and after those sessions, even if the broadcast messages for the middle sessions are lost due to network failure. These schemes are quite suitable in supporting secure communication over unreliable networks such as sensor networks and ad hoc networks. An efficient self-healing key distribution scheme is proposed in this paper. The scheme bases on the concept of access polynomial and self-healing key distribution model constructed by Hong et al. The new scheme reduces communication and computation overheads greatly yet still keeps the constant storageoverhead.